Designing the Concrete Mix Design in order to Determine the Deviation Value of the Two Concrete Compressive Test Instruments (Pressure Test and Hammer Test) - Asmadi Asmadi; Susi Haryani (Vokasi, 2020)
The role of concrete material in building structures is a very important, in the other word almost all of structural building use concrete components. Using this research, we try to ascertain how big the deviation results from the two tools. Through laboratory research that is examined from the physical coarse aggregate material, fine aggregate, we get the job mix concrete formula. the quality of the concrete that we design is concrete K-200 kg / cm2. from the results of our job mix, the proportion of the concrete mixture for 1 m3 of concrete is as follows cement 351.85 kg, sand 780.42 kg, crushed stone 1077.73 kg, water 142.34 kg, then made as many as 15 pieces of cube specimens. Then for the finished structural test object, a building is made from the structure of the foundation, loop beams, columns, floor beams and floor slabs. When casting is carried out, the making of concrete cube specimens is taken back, respectively, the number of foundation test objects is 3 concrete cubes, 3 sloop blocks of concrete cubes, 3 columns, 3 beams and 3 floor plates. The average test results of these test tools are as follows: the pressure test using the concrete pressure test device is 211 kg / cm2, and the test result using the concrete hammer test is 195 kg / cm2.